2022
DOI: 10.3390/ma15051639
|View full text |Cite
|
Sign up to set email alerts
|

Calibration and Validation of a Linear-Elastic Numerical Model for Timber Step Joints Based on the Results of Experimental Investigations

Abstract: The paper is dedicated to the numerical analysis of a single-step joint, enabling the prediction of stiffness and failure modes of both single- and double-step joints. An experimental analysis of the geometrically simplest version, the single-step joint, serves as a reference for the calibration of the subsequent finite element model. The inhomogeneous and anisotropic properties of solid timber make detailed modelling computationally intensive and strongly dependent on the respective specimen. Therefore, the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 20 publications
2
11
0
Order By: Relevance
“…These features manifest themselves at the post-peak stage of deformation due to the growth of plastic strains and, as a consequence, the appearance of an almost horizontal section on the load-displacement curve. For example, for cubic spruce specimens of 40 × 40 × 40 mm (humidity 18%) under compression along the fibers with a controlled displacement of 10 mm/min (Figure 1), experimental curves (Figure 2) were obtained (in the laboratory of the Institute of Forestry, Mining and Construction Sciences, Petrozavodsk State University), which are similar to other experimental curves of comparable tests known from the literature [30,[38][39][40]. We will analyze the behavior of wood under uniaxial compression using the plots in Figure 2 and the results of acoustic emission measurements in comparable tests known from the literature [30,33].…”
Section: Load-displacement Curve In Compression Tests Of Wood Along T...supporting
confidence: 77%
See 2 more Smart Citations
“…These features manifest themselves at the post-peak stage of deformation due to the growth of plastic strains and, as a consequence, the appearance of an almost horizontal section on the load-displacement curve. For example, for cubic spruce specimens of 40 × 40 × 40 mm (humidity 18%) under compression along the fibers with a controlled displacement of 10 mm/min (Figure 1), experimental curves (Figure 2) were obtained (in the laboratory of the Institute of Forestry, Mining and Construction Sciences, Petrozavodsk State University), which are similar to other experimental curves of comparable tests known from the literature [30,[38][39][40]. We will analyze the behavior of wood under uniaxial compression using the plots in Figure 2 and the results of acoustic emission measurements in comparable tests known from the literature [30,33].…”
Section: Load-displacement Curve In Compression Tests Of Wood Along T...supporting
confidence: 77%
“…Regarding the validity of the simulation results, we note the following. Since we consider timber as a structure [4], it is permissible to compare the dependence according to Figure 4 with the results of tests of wooden structures known from the literature [38], according to which S secant = 123 2.73 = 45.1 kN mm ; Ŝtang = 29.6 0.38 = 77.9 kN mm does not contradict Equation ( 8) and its graphical interpretation (Figure 4), according to which the condition Ŝtang S secant = 77.9…”
Section: The Highest Value Of Tangential Stiffness and Tangential Mod...mentioning
confidence: 99%
See 1 more Smart Citation
“…It can be an excellent tool for the understanding of the behavior of connections in timber structures. Dobeš 2022 [ 35 ], Braun 2022 [ 36 ], and Kupniewska 2021 [ 37 ] dealt with the calibration and validation of numerical models according to experimental tests.…”
Section: Introductionmentioning
confidence: 99%
“…An important aspect of current research is numerical modeling, which is an excellent tool for understanding the behavior of joints in wood constructions [5,6]. The numerical analysis of single-step joints, applied by Braun et al [7], made it possible to satisfactorily determine the stiffness and predict the forces at the onset of local failure of single-and double-step joints. In doing so, it was found that the prediction was more accurate for single-step joints, due to the fact that the model was calibrated for this type of joint, and that the joint itself is less susceptible to geometric inaccuracies.…”
mentioning
confidence: 99%